Grau de preservação da mata ripária no bioma caatinga a partir da biomassa acima do solo e do estoque de carbono - Sousa Júnior, Eduardo Lima de (2024)
Riparian zones perform important ecological, social and economic functions. Despite its numerous benefits, the riparian zone - also known as riparian forest - suffers from high rates of degradation, the main one being deforestation due to improper use and occupation. Due to their ecological importance and the supply of goods and services, they are considered by the Brazilian Forestry Code to be Permanent Preservation Areas - APP, in order to protect and contain the damaging effects. In view of the above, the main objective of this research was to identify the degree of preservation of riparian forest based on above-ground biomass and carbon stock in a riparian zone, and its case study is the Umbuzeiro River in the Benguê watershed (Ceará). To carry out this research, the methodology followed four stages: (i) determination of biomass and carbon stock in situ; (ii) estimation of above ground biomass by remote sensing using images from the Landsat 8 satellite; (iii) analysis of the relationship between field data and remote sensing, by means of the coefficient of determination (R²); (iv) formulation of a model for estimating biomass in the riparian zone targeted by this research and estimating biomass over the last 10 years from Landat 8 images; (v) development and application of the degree of preservation index based on above-ground biomass for the study area. Among the results of this research, biomass estimates were obtained using data from the Landsat 8 satellite, which provided a quantification of above-ground biomass, considered pertinent according to the literature. The model proposed using multiple linear regression and leave-one-out cross-validation (LOOCV) for the riparian zone of the Umbuzeiro River obtained a coefficient of determination (R² = 0.54), indicating that the model can be used to predict above-ground biomass. The dynamics of above-ground biomass over the last decade in the riparian zone of the Umbuzeiro River, carried out using 206 Landsat 8 images with coverage, available from 2013 to 2023, showed a similarity in biomass estimation between the models tested, where both were able to estimate high and low predictions for the years evaluated, a factor directly related to the influence of seasonality on the estimated average biomass value. The application of the proposed index proved to be effective in determining the degree of preservation of the riparian zone of the Umbuzeiro River in the Benguê basin, warning of the influence of anthropogenic actions on the reduction of above-ground biomass, which is directly related to the preservation of these areas. In view of this result, the importance of this tool for assessing and monitoring a river basin is highlighted.